2015
DOI: 10.2214/ajr.14.12828
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Limitations of FDG PET/CT for Imaging of Squamous Cell Carcinoma of the Head and Neck: A Comprehensive Review of Anatomy, Metastatic Pathways, and Image Findings

Abstract: Understanding the characteristics of squamous cell carcinoma of the head and neck, as imaged by FDG PET/CT, is crucial for determining treatment strategy, because it helps to avoid incorrect staging and also provides an accurate assessment of treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…The failure to detect the false-negative primary reflected the limited sensitivity of 18 FDG PET/CT, which is an inherent limitation. 27,28 Our study showed excellent sensitivity, specificity and accuracy of biomarker examinations in MCNs. We used the results of panendoscopy-guided biopsy under general anesthesia as the reference standard to compare those of nodal HPV, p16 and EBV status with 18 F-FDG PET/CT.…”
Section: Tumor Markers and Signaturessupporting
confidence: 52%
See 1 more Smart Citation
“…The failure to detect the false-negative primary reflected the limited sensitivity of 18 FDG PET/CT, which is an inherent limitation. 27,28 Our study showed excellent sensitivity, specificity and accuracy of biomarker examinations in MCNs. We used the results of panendoscopy-guided biopsy under general anesthesia as the reference standard to compare those of nodal HPV, p16 and EBV status with 18 F-FDG PET/CT.…”
Section: Tumor Markers and Signaturessupporting
confidence: 52%
“…In our study, a tumor size <1.5 cm was found in 14 (50%) of 28 occult primaries, of which only 3 (21.4%) were identified by 18 F‐FDG PET/CT scans. The failure to detect the false‐negative primary reflected the limited sensitivity of 18 FDG PET/CT, which is an inherent limitation …”
Section: Discussionmentioning
confidence: 99%
“…Head-neck tumors often go along with local inflammation. Unfortunately, a recent review reported that most original work found that 18 F-FDG PET/CT is not useful in discriminating benign from malignant tumors because of the overlap of uptake in both conditions (18)(19)(20). In this setting, 68 Ga-FAPI PET/CT may offer an advantage regarding tumor delineation-for example, in planning of radiotherapy ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 F]FDG‐PET/CT is useful for the detection of nodal disease and identifies distant metastases or a synchronous primary in up to 15% of head and neck SCC (HNSCC) cases. The quantitative degree of metabolism also has been shown to correlate with disease‐free survival …”
Section: Discussionmentioning
confidence: 99%